The immunomodulatory potential of bradykinin signaling in autoimmune conditions - Szaryńska, Magdalena; Olejniczak-Kęder, Agata (Frontiers in Immunology, 2026)
Bradykinin (BK) is a biologically active nanopeptide that plays a crucial role within the kallikrein–kinin system (KKS), a complex network involved in the regulation of vascular tone, epithelial cell ion transport, vascular permeability, mucosal secretion, release of cytokines from leukocytes among others. Over the past decades, BK has attracted sustained scientific interest due to its pleiotropic effects observed across various tissues and pathological conditions. Recent advances have significantly broadened our understanding of BK’s role in modulating inflammatory and immune processes. Notably, accumulating evidence indicates that BK can exert dual and context-dependent effects—either pro-inflammatory or anti-inflammatory—depending on the cellular environment, receptor subtype activation (BK1R vs BK2R), and crosstalk with other signaling pathways. Emerging studies highlight that BK receptors may interact with another surface molecules expressed on immune cells, including T cell receptors (TCR) and immune checkpoint proteins such as PD-L1. These interactions suggest that BK signaling may be in a center of crucial immunoregulatory mechanisms influencing leukocyte activation status. Such findings may have important implications for understanding immune homeostasis and for designing novel therapeutic strategies. In cancer, BK is suggested to contribute to tumor progression through the promotion of cancer stem cells and immunosuppressive microenvironment formation, whereas in autoimmune diseases, its modulation could attenuate excessive immune activation and tissue damage. Therefore, the dual nature of BK action positions it as both a potential therapeutic target and a modulatory agent depending on disease context. This review summarizes current knowledge on the multifaceted roles of BK in inflammation and immunity, emphasizing its molecular mechanisms, receptor dynamics, and potential therapeutic applications. Special attention is given to the interplay between BK signaling and regulatory membranous proteins, offering a framework for future research aimed at exploiting BK pathways to either suppress chronic inflammation or overcome tumor-associated immunosuppression.